KENDALA PENGAJARAN BAHASA INGGRIS DI SEKOLAH DASAR (PROBLEMS OF ENGLISH TEACHING IN ELEMENTARY SCHOOL) - Rina Listia Sirajuddin kamal (Universitas Lambung Mangkurat, 2013)
AbstractProblems of English Teaching in Elementary School. The Indonesian government hasacknowledged the importance of English by putting it into the education system for fivedecades. English has been integrated to secondary school for a long time. The Englishlanguage is exerting even stronger influence in the modern world and has become aninternational language. There are also advantages of introducing a foreign languagefor young learners. The government of Indonesia has therefore set up the policy tointroduce English language in primary schools. This policy is optional. It depends onschool and community demands. The government does not provide teachers andcurriculum. Schools and community are in charge to provide teachers, curriculum andfacilities. Teachers are one of the most important parts in the discourse of educationand the process of teaching and learning in schools. It was this that interested to researchtheir perceptions of English language teaching for primary students.Keywords: english for young learners, teachers’ perception, teaching constrainstAbstrakKendala Pengajaran Bahasa Inggris di Sekolah Dasar. Pemerintah Indonesia telahmengakui pentingnya bahasa Inggris dengan menempatkan ke dalam sistem pendidikanselama lima dekade. Bahasa Inggris telah diintegrasikan ke sekolah menengah untukwaktu yang lama . Bahasa Inggris yang mengerahkan pengaruh yang lebih kuat didunia modern dan telah menjadi bahasa internasional. Ada juga keuntunganmemperkenalkan bahasa asing untuk pelajar muda. Oleh karena itu, pemerintahIndonesia telah menyiapkan kebijakan untuk memperkenalkan bahasa Inggris disekolah dasar. Kebijakan ini bersifat opsional. Hal ini tergantung pada tuntutan sekolahdan masyarakat. Pemerintah tidak menyediakan guru dan kurikulum. Sekolah danmasyarakat bertanggung jawab untuk menyediakan guru, kurikulum, dan fasilitas.Guru adalah salah satu bagian yang paling penting dalam wacana pendidikan danproses belajar-mengajar di sekolah. Inilah yang menarik untuk meneliti persepsi merekatentang pengajaran bahasa Inggris untuk siswa SD.Kata-kata kunci: bahasa Inggris untuk pelajar muda, persepsi guru, mengajarconstrainst